Biomechanical analysis of running in the high jump - Leite, W. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of this paper is to analyze the biomechanics of running at high jump. To this study was realized a bibliographic revision. The running phase is the one which starts when the athlete is set in movement for the jump until the moment that he touches the ground with the takeoff foot in front of the bar, this phase can be divided into two parts: the running in straight line and the running in curve. On the other hand, for better understanding and due to a biomechanical complexity, the running in curve will be divided into three other parts: the three last strides, the two last strides and the last strides. Besides that, we could mention important factors for an efficient approach run: the radius of the curve, the distance and length of the takeoff run.